Improving Student Learning Outcomes Through Vidio Learning Models In Class IVA Mathematics MIS Islamiyah GUPPI Medan - Hasibuan, May Fitriana; Saragih, Marice (Journal of Classroom Action Research, 2024)
The aim of this research is to improve the mathematics learning outcomes of class IVA MIS Islamiyah GUPPI students by using a video learning model. This research is classroom action research. The data collection techniques used are conducting reviews, data collection and observation. The data collected is a test of student learning outcomes carried out in the second cycle. From the analysis of the data obtained, it can be concluded that there is a significant increase in learning outcomes after using the video learning model. It can be seen from the average (mean) value of test I, which is 76.67, while the learning results in test II have an average (mean) value of 87.33, which means there is an increase in each test carried out. So we can conclude that learning using instructional video media can improve the mathematics learning outcomes of class IVA MIS Islamiyah GUPPI students on the subject of simple fractions. Keywords : Learning Outcomes, Simple Fractions, Learning Video Models